2000
DOI: 10.1143/jjap.39.6130
|View full text |Cite
|
Sign up to set email alerts
|

Grown-in Microdefects in a Slowly Grown Czochralski Silicon Crystal Observed by Synchrotron Radiation Topography

Abstract: Grown-in microdefects of a slowly grown Czochralski (CZ) silicon crystal were studied by short wavelength synchrotron radiation topography and successfully visualized. It was shown that the microdefects had spherical strain fields, by comparing the defect images in the two topographs taken with the Bragg reflections perpendicular and parallel to the growth direction. The radial distributions of the microdefect size and density were measured from the defect images in the topographs. The misfit volume of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
5
13
0
Order By: Relevance
“…This result is well correlate with data of Ref. [26]. Such impurities as oxygen [37,55,[68][69][70][71][72][73] and carbon [12,28,67,[74][75][76][77][78] which are found in high concentrations in FZ silicon [79] render direct effect on process of formation of defects.…”
Section: Influence Of a Growth Condition And Impurities On A Defect Fsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is well correlate with data of Ref. [26]. Such impurities as oxygen [37,55,[68][69][70][71][72][73] and carbon [12,28,67,[74][75][76][77][78] which are found in high concentrations in FZ silicon [79] render direct effect on process of formation of defects.…”
Section: Influence Of a Growth Condition And Impurities On A Defect Fsupporting
confidence: 90%
“…[21] as well as results of Refs. [14,[18][19][20] also are confirmed by other recent researches [22][23][24][25][26]. Many of these Refs.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the model of point-defect dynamics cannot explain the large amount of experimental research into the defect structure of dislocation-free Si monocrystals. It follows from experiment that oxygen and carbon play a dominant role in the formation of grown-in microdefects in large-scale CZ-Si monocrystals [27][28][29][30]. Local maxima of microdefect concentrations coincide with areas of phosphor in high concentration [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another group of authors, on the grounds of their experimental results, adhere to the opposite viewpoint [2123, 33,34]. In [35] an assumption was made that the formation mechanism of grown-in microdefects is mostly influenced by the joint agglomeration of self-interstitials and carbon atoms (found in LST-defects [36]) instead of oxygen precipitation. Similar results were obtained in [37], where it was shown that OSF-rings are formed as per heterogeneous mechanism under simultaneous oxygen precipitation and agglomeration of silicon self-interstitials with atoms of non-oxygen impurity.…”
Section: Discussionmentioning
confidence: 99%